Limites e possibilidades do Ensino Médio Politécnico : um estudo em escolas de Porto Alegre - RS - Reis, Jonas Tarcísio (Universidade do Vale do Rio dos Sinos, 2018)
The commitment of this thesis is with the advancement in the field of analysis of the implementation of educational policies, to unveil the meanderings of the processes of forces correlation inherent to the dynamics of confrontation between ideas rooted in the school and ideas brought about by new policies. The general objective was to analyze the implementation of the Polytechnic High School (EMP), seeking to understand its limits and possibilities and the ideological positions present in the defense or refusal of this curricular reform implemented by the State Secretariat of Education of Rio Grande do Sul (SEDUC –RS/ BRAZIL) in the quadrennium 2011-2014. The theoretical-methodological basis of the investigation was constituted in dialectical historical materialism. The database consisted of documents published by SEDUC-RS for the implementation of the EMP, current educational legislation, semi-structured interviews with policy creators and implementers, at SEDUC-RS and at four schools in the city of Porto Alegre. For the interpretation and treatment of the data we use principles of Documentary Analysis. The thesis is divided into nine chapters including the final considerations. The results showed that: the origin of this policy lies in socialist and Popular Education (EP) fundamentals; the research in the Integrated Seminar (SI) and the Emancipatory Assessment (EA) took center stage. Many of the works carried out by the students have had approximate orientation to the concept of Socially Necessary Work created in the early years of Soviet education, helping to form subjects capable of producing an awareness that they are capable of doing what they propose as human beings. The AE also generated much controversy and ideological clashes; the schools that already had knowledge and / or experiences with the concepts inherent to the EMP obtained better results in the implementation; the ideology of meritocracy embodied in school practices, as in selective and classificatory evaluation and in content, constituted a strong resistance to implementation. However, with the EMP, the State attempted to mobilize to form emancipated subjects capable of transforming society, but failed to conquer politically and ideologically the necessary influence to reach agreement with the whole of society about its positivity, for not having the Syndicate as an ally, mainly, not having paid the National Salary Floor in the basic of the teaching career, also for having found a scenario of low incentives for pedagogical innovation in schools, with a teaching model based on the fragmented curriculum, in a banking pedagogy and a selective and classificatory evaluation. Also by barriers in teacher training, coupled with a historic lack of investments in school infrastructure. Another reason was that SEDUC-RS management had implemented the proposal without a longer time for discussions with school communities; there was a dismantling and a process of forces correlation between the new and old within the schools, being, in a certain way, a confrontation with the processes of school exclusion. This research helps to identify the intricacies of the limits and possibilities of a curricular restructuring policy aimed at promoting human emancipation in high school, against a secular meritocratic school model, aiming ultimately at the conformation of substantive equality and real social justice.
Keywords: Ensino Médio Politécnico – EMP; Política Educacional; Ideologia da Meritocracia; Reestruturação curricular; Emancipação humana; Emancipação humana; Polytechnic High School - EMP; Educational politics; Ideology of Meritocracy; Curricular restructuring; Human emancipation; ACCNPQ::Ciências Humanas::Educação